Painting With and Without Numbers: the use of qualitative and quantitative methods to study social learning - Warne, Leoni; Pascoe, Celina; Ali, Irena (Australasian Journal of Information Systems, 2005)
The Enterprise Social Learning Architecture (ESLA) team of the Defence Science and Technology Organisation (DSTO), conducted a four-year research study investigating social learning within the Australian Defence Organisation (ADO). The immediate aim of this research was to understand the issues inherent in building learning, adaptive and sustainable systems. The long-term objective was to develop architectures that would support the development of information systems to guide and enhance organisational learning and facilitate knowledge management. In this paper we will discuss the methodologies used by the ESLA team to gain understanding into effective social learning and the organisational and cultural factors that support such learning. Also, the paper will discuss the lessons learned from methodological approaches to this study as well as support tools used to analyse large volumes of qualitative data. There has been an increasing emphasis in the past decade on investigating the social and organisational factors that may underpin successful information system development and usage (Butterfield and Pendegraft, 1996; Davenport and Prusak, 1992; DeLone and McLean, 1992). Investigation of these issues necessitates a sound understanding of organisational culture, human social interactions, communication and relationships, and reflects an increasing awareness of the importance of the social aspects of socio-technical systems that people work and operate in. This paper describes the process by which the qualitative methods in this study of knowledge processes were expanded to include quantitative methods. It focuses on how this combination of data collection methods evolved, and the ways in which it was capitalised on to provide a much more enriched set of findings than would have been the case if qualitative or quantitative methods had been used alone. The paper also focuses on pitfalls that arose in the use of the various methods, including those associated with the use of software for qualitative data, and the means by which a successful methodological blend can be achieved with research relating to knowledge and its management.